Reaksi Investor terhadap Earnings Management - Bernardus Y. Nugroho (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
This paper examines investor reaction to earnings management around seasoned equity offerings (SEO) by companies listed on Indonesia Stock Exchange (IDX) in the period 2005-2007. Using Jones Model modified by Dechow (1995), this research found evidence of earnings management around seasoned equity offerings. Based on managerial response hypotesis, this research analyze whether SEO announcement signals earnings management to investor. Furthermore, this research also analize investor reaction on SEO announcement and financial report around SEO. The result shows that investor failed to recognize earnings management on financial report before SEO. However, this research does not found evidence that SEO signals earnings management conducted by firms to investor.Keywords: Earnings management, seasoned equity offerings, investor reaction, managerial response hypothesis